2018
DOI: 10.1021/acsami.8b04724
|View full text |Cite
|
Sign up to set email alerts
|

Power Dissipation of WSe2 Field-Effect Transistors Probed by Low-Frequency Raman Thermometry

Abstract: The ongoing shrinkage in the size of two-dimensional (2D) electronic circuitry results in high power densities during device operation, which could cause a significant temperature rise within 2D channels. One challenge in Raman thermometry of 2D materials is that the commonly used high-frequency modes do not precisely represent the temperature rise in some 2D materials because of peak broadening and intensity weakening at elevated temperatures. In this work, we show that a low-frequency E shear mode can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 42 publications
1
51
0
Order By: Relevance
“…It was also shown that increasing the number of boron nitride layers (to a total thickness of 12.8 nm) led to a reduction of as much as ≈50% in the measured h K . Tungsten diselenide on SiO 2 substrate showed similar thickness dependent behavior as reported by Behranginia et al via an electronic‐heating Raman‐probe platform. However, the conductance was shown to peak for 3 to 4 layers of WSe 2 with a value of 32 MW m −2 K −1 .…”
Section: Thermal Boundary Conductance Across Interfaces Composed Of 2mentioning
confidence: 99%
“…It was also shown that increasing the number of boron nitride layers (to a total thickness of 12.8 nm) led to a reduction of as much as ≈50% in the measured h K . Tungsten diselenide on SiO 2 substrate showed similar thickness dependent behavior as reported by Behranginia et al via an electronic‐heating Raman‐probe platform. However, the conductance was shown to peak for 3 to 4 layers of WSe 2 with a value of 32 MW m −2 K −1 .…”
Section: Thermal Boundary Conductance Across Interfaces Composed Of 2mentioning
confidence: 99%
“…As high performance and low power devices are more in need to meet the harsh requirements of the emerging mobile and Internet of Things (IoT) environment, it becomes clear that energy dissipation and electrical breakdown are formidable challenges, toward the realization of further miniaturization and functionalized integration of 2D electronics 7–12. Power dissipation in 2D materials, including graphene, black phosphorus, and other TMDCs, has been studied by Raman spectroscopy under the high electrical fields applied to the FET structure 11,13–16. To the best of our knowledge, the power dissipation and electrical breakdown of molybdenum ditelluride (MoTe 2 ) have not been studied intensively, although it is one of the most promising TMDCs that can be employed for future 2D device applications requiring ambipolar semiconducting properties 17–20.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous measurement of electrical currents and Raman shifts on 2D materials enables to reveal the temperature profile of 2D materials induced by the Joule heating. It is obviously important to examine the energy dissipation of 2D electronics and the thermal state on their surface under electrical biasing 11,13–16. In this work, we investigated the electrical breakdown and phase transition of MoTe 2 , and examined the effects of voltage and temperature on Raman shifts from various thickness MoTe 2 transistors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations